Implementation of Multi-Agent Energy Management for Secondary Control of a Microgrid - Yoldas, Yeliz; Onen, Ahmet; Alawasa, Khaled; El Haffar, Abdelsalam; Ahshan, Razzaqul; Islam, Md Rabiul; Muyeen, S. M.; Noorfatima, Nadya; Jung, Jaesung (2023 IEEE International Conference on Applied Superconductivity and Electromagnetic Devices, ASEMD 2023, 2023)
The multi-agent energy management system (EMS) is needed to coordinate multiple agents of a microgrid to provide efficient operation of the system. In this study, multi-agent EMS is seen as the middle controller between primary and tertiary control levels. It is responsible for determining the relevant set points based on data gathered from the tertiary control level and sending them to the appropriate primary control level agents. The main objective of this paper is to propose a new optimization model for multi-agent EMS to minimize errors between the forecasted and real-time data at every predetermined time interval. Rather than using a traditional centralized microgrid controller to determine the dispatch of resources, a new framework-based multi-agent coordination is proposed to achieve the following objectives: minimizing load shedding, maximizing load dispatch and reliability, providing frequency, and maintaining voltage stability.
Keywords: Control level; Dynamic energy managements; Microgrid; Multi agent energy management; Multiple agents; Optimal controls; Point-based; Primary control; Secondary control; Setpoints; Dynamic energy management; microgrid; optimal control; secondary control